Brain structure of Scutigera coleoptrata: New insights into theevolution of mandibulate olfactory centres : short communication - Sombke, Andy; Harzsch, Steffen; Hansson, Bill S. (Soil Organisms, 2009)
Myriapods represent an arthropod lineage, originating from a marine arthropod ancestor that most likely conquered land independently from hexapods. The successful transition from marine to terrestrial life requires a number of physiological adaptations important for survival out of water. The sensory organs of terrestrial species must be able to function in air rather than in water. In chemoreception, establishing aerial olfaction requires molecules to be detected in gas phase instead of in water solution. In general, the neuroethology of myriapods and the architecture of their central nervous systems are poorly understood. In a set of preliminary experiments with the centipede Scutigera coleoptrata, we analysed the central olfactory pathway with serial semi-thin sectioning combined with 3D reconstruction, antennal backfilling with neuronal tracers, and immunofluorescence combined with confocal laser-scanning microscopy. These experiments indicate that S. coleoptrata possess the neuronal substrate for a good sense of aerial olfaction. However, the architecture of its olfactory system is clearly distinct from hexapods and also from terrestrial crustaceans, indicating independent evolution of its olfactory sense.